Correlation of Natural Gases from the X Field of the Niger Delta, Nigeria - Takyi, Botwe; Selegha, Abrakasa; Godwin, Udom J; Eugene, Kouadio Koffi (International Journal of Geography and Geology, 2020)
The molecular and isotopic composition of thirteen (13) natural gas samples from 13 producing wells of the “X” Field of the Niger Delta, Nigeria was used for this study. The study is aimed at establishing the genetic relationship between natural gases and classifying them into genetic families. The Gas chromatographic technique was used to determine the molecular composition of the natural gases using GPA 2286, as a standard test method. The carbon isotopic compositions for C1, C2, and C3 were computed using regression formulas. The results indicate that the natural gas is dominated by methane with an average dryness coefficient (C1/C1-5*100) of 95.61%, with minor amounts of CO2 = 1.48%, N2 = 0.22%. The H2S content of the samples was below the detection limit of 0.20 ppm. The δ13C1 values range from -43.63‰ to -37.64 ‰, with an average of -40.79‰. The average carbon isotopic composition for the heavy hydrocarbon gases: ethane (δ13C2) and propane (δ13C3) are -27.47‰ and -28.15‰ respectively. The results also indicate that 11 samples out of the 13 studied samples are genetically related, implying that they were generated by the same source rock at almost the same temperature and pressure conditions. The 2 samples S1 and S7 that showed a significant difference in the isotopic and molecular composition may be as a result of a flow barrier between these two wells and the other 11 wells within the reservoir. The natural gases are genetically related and were generated by the same source rock.